2022
DOI: 10.1038/s41467-022-32515-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct control of lysosomal catabolic activity by mTORC1 through regulation of V-ATPase assembly

Abstract: Mammalian cells can acquire exogenous amino acids through endocytosis and lysosomal catabolism of extracellular proteins. In amino acid-replete environments, nutritional utilization of extracellular proteins is suppressed by the amino acid sensor mechanistic target of rapamycin complex 1 (mTORC1) through an unknown process. Here, we show that mTORC1 blocks lysosomal degradation of extracellular proteins by suppressing V-ATPase-mediated acidification of lysosomes. When mTORC1 is active, peripheral V-ATPase V1 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 60 publications
(97 reference statements)
5
34
0
Order By: Relevance
“…Lysosomal v-ATPase consists of both V0 and V1 domains that are associated with the lysosomal membrane and faced the cytosol, respectively. Reversible dissociation of the V1 and V0 domains responds to nutritional signals and plays a crucial role in the regulation of the lysosomal v- ATPase activity (Kane, 1995; McGuire & Forgac, 2018; Ratto et al, 2022; Stransky & Forgac, 2015). Except for VHA-18 (V1 H subunit), we were able to detect all other subunits of lysosomal v-ATPase, including VHA-5, 6, 7 and UNC-32 (V0 a subunits), VHA-1, 2, 3 and 4 (V0 c subunits), VHA-16 (V0 d subunit), VHA-17 (V0 e subunit), VHA-13 (V1 A subunit), VHA-12 (V1 B subunit), VHA-11 (V1 C subunit), VHA-14 (V1 D subunit), VHA-8 (V1 E subunit), VHA-9 (V1 F subunit), VHA-10 (V1 G subunit), and VHA-15 (V1 H subunit), and also two v-ATPase transporting accessory proteins, VHA-19 and VHA-20 (Figure 2D, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomal v-ATPase consists of both V0 and V1 domains that are associated with the lysosomal membrane and faced the cytosol, respectively. Reversible dissociation of the V1 and V0 domains responds to nutritional signals and plays a crucial role in the regulation of the lysosomal v- ATPase activity (Kane, 1995; McGuire & Forgac, 2018; Ratto et al, 2022; Stransky & Forgac, 2015). Except for VHA-18 (V1 H subunit), we were able to detect all other subunits of lysosomal v-ATPase, including VHA-5, 6, 7 and UNC-32 (V0 a subunits), VHA-1, 2, 3 and 4 (V0 c subunits), VHA-16 (V0 d subunit), VHA-17 (V0 e subunit), VHA-13 (V1 A subunit), VHA-12 (V1 B subunit), VHA-11 (V1 C subunit), VHA-14 (V1 D subunit), VHA-8 (V1 E subunit), VHA-9 (V1 F subunit), VHA-10 (V1 G subunit), and VHA-15 (V1 H subunit), and also two v-ATPase transporting accessory proteins, VHA-19 and VHA-20 (Figure 2D, Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…How PI3K regulates V0-V1 assembly has not been elucidated, but two molecules have recently been reported to be involved in its regulation.Rabconnectin-3, which play a role of chaperon to take free V1 to lysosomal membrane engaged V0, is involved in the reassembly ( 63 ). Another is TRiC, which functions to hold the V1 complex in cytosol ( 68 ). In sepsis, the inability of the lysosomal system to adequately respond to excessive bacterial load could be a factor in early mortality, and the dysfunction of V0-V1 ATPase assembly might be the molecular mechanism responsible for this inability.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for reversible disassembly as a regulatory mechanism has also been found in higher organisms, including in human cells. [16][17][18][19] Here, the process is fine-tuned to the need for proton pumping in specific tasks such as maturation of dendritic cells, [20] TOR signaling, [21,22] neurotransmitter loading into synaptic vesicles, [23] and nutrient sensing. [24] While the process of reversible disassembly has been extensively characterized on the cellular level in yeast, [25] our understanding of the molecular events that trigger the disassembly or reassembly on the level of the enzyme is only now beginning to emerge.…”
Section: F I G U R Ementioning
confidence: 99%
“…Subsequent studies, however, have painted a more nuanced picture as several environmental con-ditions were identified that had no obvious link to glucose or ATP levels under which the degree of assembly was significantly altered, such as elevated extracellular pH or salinity. [15,88] V-ATPase reversible disassembly was subsequently found to be conserved in higher animals including mammals, with reversible disassembly observed in specific enzyme populations and/or processes such as dendritic cell maturation, [20] TOR signaling, [21,22] synaptic vesicle loading, [23] and glucose metabolism. [24] Of note, conditions that triggered enzyme disassembly in yeast (glucose starvation) [14] were in some cases conditions that led to the opposite result in mammalian cells, [24] pointing to the convergence of diverse signaling pathways at the level of the enzyme.…”
Section: V-atpase Regulation By Reversible Disassemblymentioning
confidence: 99%